The reactions of triplet and singlet methylene. - Generosa, John I. (University of Ottawa (Canada), 1964)
The reactions of singlet and triplet methylene with butene-2 in the presence of inert gases (Ar, CF4, He, N2 and Xe) have been studied. Singlet methylene (generated from the photolytic decomposition of diazomethane), upon colliding with a non-reactive gas readily undergoes a transition to the lower energy triplet methylene. At low pressures of inert gas the reactions are due to singlet, while in high pressure regions triplet methylene is the reactant. Plots of product yield vs. inert gas pressure show distinct trends in these pressure regions. Triplet methylene makes its appearance known at an inert gas-butene ratio of about 550, whereupon distinct inflections of pressure dependent curves occur. Cis-pentene-2 and 2-methylbutene-2 are formed by singlet methylene insertion in C-H bonds. 3-methylbutene-l and trans-pentene-2 are products of the triplet reaction, but appear in the singlet region as well. Cis- and trans-1,2-dimethylcyclopropane are unequivocally shown to be products of triplet methylene addition to the double bond, while the cis-compound (only) is directly formed by singlet methylene addition across the double bond. Direct insertion by triplet methylene does not occur, nor does triplet methylene abstract hydrogen atoms, although triplet intermediates may do so intramolecularly. Triplet methylene reacts with molecular oxygen much more rapidly than singlet methylene does. Attempts to directly generate triplet methylene by mercury photosensitization of diazomethane was unsuccessful owing to direct absorption of the resonance line by diazomethane. It has been shown conclusively that the products formed result from methylene-butene reaction and not from diazomethane-butene reaction, although the products formed in either case are the same. The thermal reaction (225°C) of diazomethane with cis-butene-2 in the presence of inert gas was studied. The products formed are due to a butene-diazomethane adduct, and not from free methylene reaction. A theoretical treatment of the spin-orbit perturbation reveals that the spontaneous transition from the singlet to the triplet state of methylene occurs at a rate of 2.2 x 1013 sec.-1. The spin-orbit perturbation found in methylene has been calculated to be 130 small calories.
Keywords: Chemistry, Organic.